From Batoni's brush to Canova's chisel: painted and sculpted portraiture at Rome, 1740-1830 - O'Dwyer, Maeve Anne (The University of Edinburgh, 2017)
This thesis examines the city of Rome as a primary context of British sociability and portrait identity during the period from 1740 to 1830. Part I considers the work of the portrait painter Pompeo Batoni. It examines the pictorial record of grand tourist sociability at Rome in the 1750s, questioning the complex articulation of nationality among British visitors, and the introduction of overt references to antiquity in the portraiture of Pompeo Batoni. It subsequently interrogates Batoni's use of the partially nude Vatican Ariadne sculpture in five portraits of male grand tourists, dating from Charles John Crowle in 1762, to Thomas William Coke in 1774. Part II of this thesis considers the realities of viewing the sculpted body at Rome, recreating the studios of sculptors Christopher Hewetson and Antonio Canova. It postis the studio space as a locus of sociability for British visitors to Rome, drawing on the feminine gaze in the form of the early nineteenth-century writings of Charlotte Eaton and Lady Murray. The final chapter moves from the focus on British sitters to examine sculpture by Antonio Canova, framing it within a wider discourse of masculinity and propriety. Thte reception of Canova's nude portrait sculpture of Napoleon Bonaparte and Pauline Borghese is considered as indicative of cultural anxieties stemming from new conceptions of gender.
Keywords: Batoni; Canova; portrait; studio; reception; nineteenth-century; eighteenth-century; Hewetson; Grand Tour; classical sculpture; Rome